Exploring Solutions to Mitigate Unidirectional Grain Growth and to Set Operational Envelop for Wire + Arc Additive Manufacturing of Aluminium Alloys - Yehorov, Yurii (2018)
Wire Arc Additive Manufacturing (WAAM) is a novel process with high industrial application. However, there are still some limitations, such as anisotropy of mechanical properties, which delays a wide implementation of WAAM. Moreover, as long as WAAM is a new technology, its operational envelope is not utterly known. The first objective of this work was to assess solutions to mitigate unidirectional grain growth in WAAM of aluminium, that leads to anisotropy of the mechanical properties of the printed part. In the scope of this objective, two methodological approaches were employed. The first approach used the switchback welding technique in comparison with a reference (the conventional unidirectional deposition) and also a traditional method for reduce unidirectional growth (bidirectional deposition). The second one used nanoparticles inoculation in the deposited metal. Both approaches showed ability to mitigate epitaxial growth of big columnar grains and to refine microstructure, however switchback technique show to be easier to implement. The second objective of this work was to find an operational envelope of the process, i.e., a range of travel speeds for a given deposition rate and for a given ratio deposition rate/travel speed. This study showed there are a range of pool volume during the deposition that must be respected to reach sound printed walls.